Faktor – Faktor Yang Mempengaruhi Impor Beras Di Indonesia Tahun 2015 – 2021 - Istifaria Inka Handini; Muhammad As’ad (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study was to analyze the effect of product quality and price on residential product purchase decision at PT Lentera Indonesia Sejahtera North Tambun. The research method used was a quantitative method. The data collection techniques were in the form of questionnaires and literature. The population of this study was consumers who had taken or had a housing credit agreement at the Green Srimahi Residence 2 PT Lentera Indonesia Sejahtera North Tambun. The sampling technique in this study was non-probability sampling with the Census Sample method (saturated sample) with 68 samples. The analysis of the data used was a multiple linear regression analysis using IBM Statistic software version 28. The results showed that, partially, there was a positive and significant effect of the Product Quality variable on Purchase Decision by 63.4%, partially, there was a positive and significant effect of the Price variable on Purchase Decision by 66.3%, partially, there was a positive and significant effect of the Product Quality and Price variables on Purchase Decision by 72.1%, the remaining 29.9% was explained by other variables not examined in this study.